Immunocytochemical localization of V‐H+‐ATPase, Na+/K+‐ATPase, and carbonic anhydrase in gill lamellae of adult freshwater euryhaline shrimp Macrobrachium acanthurus (Decapoda, Palaemonidae). Issue 7 (2nd June 2015) - Maraschi, Anieli Cristina; Freire, Carolina Arruda; Prodocimo, Viviane
ABSTRACT Physiological (organismal), biochemical, and molecular biological contributions to the knowledge of the osmoregulatory plasticity of palaemonid freshwater shrimps has provided a fairly complete model of transporter localization in their branchial epithelium. Direct immunological demonstration of the main enzymes in the gill epithelia of adult palaemonids is, however, still incipient. The diadromous freshwater shrimp Macrobrachium acanthurus was exposed to increased salinity (25‰ for 24 hr), and its responses at the systemic level were evaluated through the assays of hemolymph osmolality and muscle hydration, and at cellular and subcellular levels through the activity and localization of the V‐H+‐ATPase, the Na+/K+‐ATPase, and the carbonic anhydrase. Results showed an increase in hemolymph osmolality (629 ± 5.3 mOsm/kg H2O) and a decrease in muscle hydration (73.8 ± 0.5%), comparing values after 24 hr in 25‰ with control shrimps in freshwater (respectively 409.5 ± 15.8 mOsm/kg H2O and 77.5 ± 0.4%). V‐H+‐ATPase was localized in pillar cells, whereas Na+/K+‐ATPase in the septal cells. The main novelty of this study was that carbonic anhydrase was localized in the whole branchial tissue, in pillar and septal cells. Exposure to high salinity for 24 hr led to no detectable changes in their localization or in vitro activity. Immunolocalization data corroborated the literature and current models of palaemonid gill ion transport. The absence of changes reinforces the need for the constant expression of these enzymes to account for the euryhalinity of these shrimps. J. Exp. Zool. 323A: 414–421, 2015. © 2015 Wiley Periodicals, Inc.